2002
DOI: 10.1006/dbio.2002.0628
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dnmt1 Methyltransferase Expression and Intracellular Localization during Oogenesis and Preimplantation Development

Abstract: The imprinting of mammalian genes depends on the maintenance of DNA methylation patterns during pre- and postimplantation development. Dnmt1o is a variant form of the somatically expressed Dnmt1 cytosine methyltransferase that is synthesized and stored in the oocyte cytoplasm and trafficks to the eight-cell nucleus during preimplantation development, where it maintains DNA methylation patterns on alleles of imprinted genes. Transcripts encoding Dnmt1 are present in preimplantation embryos, suggesting that Dnmt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
142
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 28 publications
14
142
1
2
Order By: Relevance
“…It was shown that DNMT1o was the only form of DNMT1 expressed in oocytes and preimplantation mouse embryos (Ratnam et al 2002) and it was initially postulated to play an important role in the acquisition of methylation patterns in oocytes. However, when Dnmt1o was subsequently knocked out in a mouse model, examination of gene-specific DNA methylation, as well as nuclear transplantation experiments, definitively showed that DNMT1o is not required for the establishment of methylation patterns in oocytes (Howell et al 2001).…”
Section: Mechanismsmentioning
confidence: 99%
“…It was shown that DNMT1o was the only form of DNMT1 expressed in oocytes and preimplantation mouse embryos (Ratnam et al 2002) and it was initially postulated to play an important role in the acquisition of methylation patterns in oocytes. However, when Dnmt1o was subsequently knocked out in a mouse model, examination of gene-specific DNA methylation, as well as nuclear transplantation experiments, definitively showed that DNMT1o is not required for the establishment of methylation patterns in oocytes (Howell et al 2001).…”
Section: Mechanismsmentioning
confidence: 99%
“…Dnmt1o is produced by the usage of an oocyte-specific promoter and first exon (Mertineit et al, 1998), which is not present in Dnmt1s and limits the expression of Dnmt1o to oocytes and early embryos. Furthermore, the activity of Dnmt1o is regulated by a nuclear sequestration mechanism that controls the retention of Dnmt1o in the cytoplasm of embryonic cells at all stages of early development with the exception of the 8-cell stage when it translocates into the nucleus maintaining DNA methylation patterns of imprinted genes (Ratnam et al, 2002). Dnmt1s (190,000 Da) expression initiates at the peri-implantation stage and is ubiquitous to all somatic cells (Mertineit et al, 1998;Trasler et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…To allow for efficient methylation removal, the maintenance DNA methyltransferase-1 (DNMT1) is largely excluded from the nuclei of the cleavage-stage embryos (Howell et al 2001;Ratnam et al 2002;Branco et al 2008;Hirasawa et al 2008). However, this compartmentalization and nuclear exclusion cannot be complete, as genetic deletion of both maternal and zygotic Dnmt1 results in imprinting defects, the result of complete ICR demethylation (Hirasawa et al 2008).…”
Section: The Trim28-complex Function In Genomic Imprintingmentioning
confidence: 99%